Iowa RBA, December 1, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for December 1, 1997. Highlights of the update include sightings of a Townsend's Solitaire, White-winged Crossbills, a male Long-tailed Duck, numerous Common Redpolls, and one Hoary Redpoll. Other observations of note include a first year Glaucous Gull, a Pacific Loon, a Western Grebe, and a female Pine Grosbeak. Also included are handwritten notes for the next week's update with a sighting of a Varied Thrush. Epson - sheet feed/flatbed